Implementation of Construction Safety Plan in The Building Project - Hadi, Patria Yoga Pratama; Soetjipto, Jojok Widodo; Trisiana, Anita (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
Data on work accidents in the construction industry in Indonesia is still relatively high, so the government issued a Construction Safety Management System (CSMS) regulation in 2021. However, many middle to lower-class contractors still need help compiling it. Contractors still use job safety analysis as a substitute for the Construction Safety Plan (CSP) with minimal analysis. Therefore, it is necessary to research the preparation of CSP, which is integrated with the project technique method. The research method used is to describe CSP implementation in selected project cases. The study results show that contractors already have good resources and commitment to carrying out CSP but have limitations in understanding the techniques for preparing CSP documents accompanied by sound risk management analysis.